American Economic Journal Applied Economics
American Economic Journal: Applied Economics publishes papers covering a range of topics in applied economics, with a focus on empirical microeconomic issues. In particular, we welcome papers on labor economics, development microeconomics, health, education, demography, empirical corporate finance, empirical studies of trade, and empirical behavioral economics.
Keywords: ECONOMÍA--PUBLICACIONES SERIADAS